Soft power of the European Union mastering the language of power politics - Juška, Žygimantas (Contributions to international relations, 2024)
This book sheds light on the complexities of the European Union's (EU) influence in a world dominated by global power politics. Written by an EU diplomat, it explores the dynamic landscape of soft power, with a focus on key regions such as the Western Balkans, Eastern Partnership, Southern Neighborhood, and Sub-Saharan Africa. Presenting the economic, diplomatic, and cultural dimensions, the book critically evaluates the EU's effectiveness in shaping behavior amid intensifying global power competition.With a unique perspective gained from on-the-ground experience in Kosovo, Ukraine, and Rwanda, the author navigates the EU's responses to challenges, including Russia's hard power approach. A must-read for policymakers and diplomats, this book blends academic analysis with practical insights, offering valuable lessons and recommendations for mastering the language of power in today's global politics. Ideal for students and professionals, it provides a comprehensive explorationof EU foreign policy dynamics